Human Development - Papalia, Diane E. [et al.] (New York McGraw-Hill, 2016)
Human development, ninth edition, is an accessible and applied 4-color text for the chronological human development course. With the help of professional writer, ruth feldman, this author team combines up-to-date research coverage with the broadest array of parenting, nursing, and education applications available. It includes coverage of social policy, cross-cultural topics, and issues facing a diverse population, as well as extensive examples relating to health issues and applications.
Includes illustrations, Bibliography References and Index.
Keywords: Developmental psychology